2009
DOI: 10.1007/s12562-009-0193-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activities of medaka Oryzias latipes peroxisome proliferator-activated receptors and their gene expression profiles at different temperatures

Abstract: Medaka Oryzias latipes peroxisome proliferator-activated receptors (PPARs) a1, a2, b, and c were characterized for their sequence structures and transcriptional activities. While the genes encoding PPARa2, b, and c were determined for their full length, the PPARa1 gene remained undetermined for its 5 0 -end region, which encodes the DNA-binding domain and a part of ligandbinding domain. Transcriptional activities of medaka PPARa2, b, and c were also examined by reporter assay using reporter plasmids containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Similarly, using both PPARα isoforms from the torafugu pufferfish for transfections in a goldfish cell line, Kondo et al [ 25 ] also demonstrated the activation of the receptors by fatty acids, Wy-14643, and ETYA and, furthermore, showed a small but significant activation of PPARαb by rosiglitazone. Similar results were also reported for the medaka ( Oryzias latipes ) PPARαa [ 63 ].…”
Section: The Functional Domains Of Fpparssupporting
confidence: 88%
“…Similarly, using both PPARα isoforms from the torafugu pufferfish for transfections in a goldfish cell line, Kondo et al [ 25 ] also demonstrated the activation of the receptors by fatty acids, Wy-14643, and ETYA and, furthermore, showed a small but significant activation of PPARαb by rosiglitazone. Similar results were also reported for the medaka ( Oryzias latipes ) PPARαa [ 63 ].…”
Section: The Functional Domains Of Fpparssupporting
confidence: 88%
“…Nuclear receptors can interact, either directly or indirectly, with epigenetic modifiers that control plastic responses to environmental signals (Legrand et al ., 2019). They can thereby upregulate or downregulate entire transcriptional programmes in response to environmental cues, such as temperature (Kondo et al ., 2009).…”
Section: Signalling Pathwaysmentioning
confidence: 99%
“…It typically induces an increase in mitochondrial volume (Egginton and Sidell, 1989;Johnston, 1982;Tyler and Sidell, 1984), mitochondrial enzyme activity and transcript levels (Battersby and Moyes, 1998;Itoi et al, 2003;Kikuchi et al, 1999;Kondo et al, 2010). We focused on COX because of its critical role in oxidative phosphorylation (OXPHOS) (Villani and Attardi, 2000), the wealth of knowledge about the function of its individual subunits, and the distinctions between the repertoire of isoforms in fish and mammals (Little et al, 2010).…”
Section: Introductionmentioning
confidence: 99%